2021
DOI: 10.1063/5.0040649
|View full text |Cite
|
Sign up to set email alerts
|

Informing NMR experiments with molecular dynamics simulations to characterize the dominant activated state of the KcsA ion channel

Abstract: As the first potassium channel with an x-ray structure determined, and given its homology to eukaryotic channels, the pH-gated prokaryotic channel KcsA has been extensively studied. Nevertheless, questions related, in particular, to the allosteric coupling between its gates remain open. The many currently available x-ray crystallography structures appear to correspond to various stages of activation and inactivation, offering insights into the molecular basis of these mechanisms. Since these studies have requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Protein-free liposomes were also examined to confirm the resonances arising from lipids. From this comparison, we concluded that much of the protein signal in spectra of the full- [3,23,26,27] or Baldus Group ( †) [25,28,29]. Structural regions are indicated to the right of residue numbers.…”
Section: Hr-mas Selectively Detects Signals From the Kcsa C-terminusmentioning
confidence: 94%
See 1 more Smart Citation
“…Protein-free liposomes were also examined to confirm the resonances arising from lipids. From this comparison, we concluded that much of the protein signal in spectra of the full- [3,23,26,27] or Baldus Group ( †) [25,28,29]. Structural regions are indicated to the right of residue numbers.…”
Section: Hr-mas Selectively Detects Signals From the Kcsa C-terminusmentioning
confidence: 94%
“…Figure 1. Solid-state NMR backbone assignments of KcsA in liposomes as described by the McDermott Group (*)[3,23,26,27] or Baldus Group ( †)[25,28,29]. Structural regions are indicated to the right of residue numbers.…”
mentioning
confidence: 99%
“…Ion channels play crucial roles in biological processes and have been thoroughly studied via MD simulations to better comprehend the molecular forces driving ion transport, flux, and selectivity. [36][37][38][39][40][41] Here, we studied the double mutant (D66Y and N68D) NaK2K reported by Derebe et al 28 and derived from the NaK channel family to demonstrate the electric field organization throughout the channel core.…”
Section: Nak2k Ion Channelmentioning
confidence: 99%
“…Meanwhile, solid and solution-state NMR studies on KcsA and KirBac1.1 have interpreted chemical shift perturbation data as supporting the two state HBC gating model [10][11][12][13][14][15] . However, in the case of KirBac3.1 it was later demonstrated that inner helix bundle stabilized with disulfide bonds in a closed conformation still allows K + ion conduction 16 and NMR chemical shift guided structural investigation of the conductive conformation of KcsA suggested a much narrower HBC opening than initially believed from the X-ray structures 17 . The struggle of assigning structures with different HBC conformations to functional states continues with more recent EM structures, as exemplified by the TASK channel 18,19 , where structural interpretations do not necessarily agree with the functional data and a residue far away from HBC appears to be critical for gating 20 .…”
Section: Introductionmentioning
confidence: 96%
“…Unlike solid-state NMR 43 spectra of NaK in liposomes, solution state NMR spectra of NaK samples in lipid bicelles display clear resonances for residues throughout the M 2 helix, including those near the HBC 44 . Additionally, while substantial attention has been paid to investigating KcsA by both solution and solid-state NMR, these studies largely excluded detailed investigation of the HBC, only indirectly correlating chemical shift perturbation data with hypothesized changes in the structure 12,14,17 : in part due to the ambiguity of the detailed atomic structures of different states 17 . While a powerful technique for unraveling structure and dynamics in smaller proteins, for large molecular systems such as ion channels, obtaining the high quality NMR data necessary for meaningful interpretation can be a challenge.…”
Section: Introductionmentioning
confidence: 99%